University Students' Views on the Efficacy of a Museum’s Historical School Lessons– The Case of Ancient Emona - Govekar Okoliš, Monika (Revija za elementarno izobraževanje, 2022)
Museums today engage in a range of educational activities, including simulated museum's historical school lessons. The article uses the Slovenian School Museum as an example and describes the education it offers, especially concerning museum's historical school lessons. The purpose of this qualitative study is to explore the views and reactions of university students (n = 19) from the Faculty of Arts at the University of Ljubljana, concerning what they learned from the enactment of a historical school lesson. An open-ended type of questionnaire was given to participants in the study year 2019/20 and used to evaluate the “Ancient Emona” school lesson. The study's findings show the historical school lesson conducted in the museum to be an effective, living, and active means of education on the history of teaching for university students.
Keywords: museum education, museum's school lessons, Slovenian School Museum, university students, Ancient Emona